Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 5 - Number Theory and the Real Number System - Chapter Summary, Review, and Test - Review Exercises - Page 335: 74



Work Step by Step

Simplify each radical to obtain: $=\sqrt{3} - 6\sqrt{9(3)} \\=\sqrt{3}-6\sqrt{3^2(3)} \\=\sqrt3 - 6(3)\sqrt3 \\=\sqrt3-18\sqrt3 \\=\sqrt3(1-18) \\=\sqrt3(-17) \\=-17\sqrt3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.